Predictive Value of Eosinophil Count on COVID-19 Disease Progression and Outcomes, a Retrospective Study of Leishenshan Hospital in Wuhan, China. (March 2022) - Xuan, Wei; Jiang, Xuliang; Huang, Lili; Pan, Shuting; Chen, Caiyang; Zhang, Xiao; Zhu, Hui; Zhang, Song; Yu, Weifeng; Peng, Zhiyong; Su, Diansan
Background: The potential protective role of eosinophils in the COVID-19 pandemic has aroused great interest, given their potential virus clearance function and the infection resistance of asthma patients to this coronavirus. However, it is unknown whether eosinophil counts could serve as a predictor of the severity of COVID-19. Methods: A total of 1004 patients with confirmed COVID-19 who were admitted to Leishenshan Hospital in Wuhan, China, were enrolled in this study, including 905 patients in the general ward and 99 patients in the intensive care unit (ICU). We reviewed their medical data to analyze the association between eosinophils and ICU admission and death. Results: Of our 1004 patients with COVID-19, low eosinophil counts/ratios were observed in severe cases. After adjusting for confounders that could have affected the outcome, we found that eosinophil counts might not be a predictor of ICU admission. In 99 ICU patients, 58 of whom survived and 41 of whom died, low eosinophil level was an indicator of death in severe COVID-19 patients with a cutoff value of 0.04 × 10 9 /L, which had an area under the curve of 0.665 (95% CI = 1.089-17.839; P = .045) with sensitivity and specificity of 0.569 and 0.7317, respectively. Conclusion: Our research revealed that a low eosinophil level is a predictor of death in ICU patients rather than a cause of ICU admission.